1982
DOI: 10.1139/y82-212
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative analysis of renal ammoniagenesis and energy balance: a theoretical approach

Abstract: Many theories have been proposed to explain the regulation of renal ammoniagenesis during chronic metabolic acidosis but none of these is entirely satisfactory. Since the activity of each of the enzymes in this pathway greatly exceeds the maximum rate of ammonium production in vivo, even when physiological substrate concentrations are used in this calculation, it follows that ammoniagenesis must be inhibited in the intact animal. We shall present a novel hypothesis for the regulation of the maximum rate of amm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1989
1989
2002
2002

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 5 publications
0
19
0
Order By: Relevance
“…To synthesize NH4+, glutamine is extracted from the glcsmemlar filtrate and the peritubular blood (Lemieux et d. 1974;Pilkington et al 1970). Metabolism s f glutamine to produce NH4+ is a process that yields, ultimately, bicarbonate and ATP as products (Halperin et al 1982). For net gain sf bicarbonate for the body, NH4+ must be made an endproduct of metabolism; this occurs when the cation NH4+ is excreted in the urine (Halperin and Jungas 1983).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To synthesize NH4+, glutamine is extracted from the glcsmemlar filtrate and the peritubular blood (Lemieux et d. 1974;Pilkington et al 1970). Metabolism s f glutamine to produce NH4+ is a process that yields, ultimately, bicarbonate and ATP as products (Halperin et al 1982). For net gain sf bicarbonate for the body, NH4+ must be made an endproduct of metabolism; this occurs when the cation NH4+ is excreted in the urine (Halperin and Jungas 1983).…”
Section: Discussionmentioning
confidence: 99%
“…1982). Since cells contain such a tiny quantity of the precursor of ATP, ABP, continued flux in pathways that produce ATP can only occur if ATP is reconverted to ADDP (Flatt 1972;Halperin et al 1982;Jungas et al 1992). This occurs in the kidney primarily when sodium is reabsorbed (flux through Na-K ATPase) (Halperin et d. 2982).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of oxidation of β-HB – or glutamine (production of NH 4 + ) by the kidney depends on the rate of generation of ADP in that organ [16]. ADP is generated when ATP is used to perform renal work (reabsorbing filtered Na + , fig.…”
Section: Concept 1: H+ Are Added To the Body When There Is A Net Incrmentioning
confidence: 99%
“…Several authors have demonstrated that glutamine may be converted into glucose and C02 by rat proximal tubules or slices in vitro (Kamm & Strope, 1972;Baverel & Lund, 1979;Watford et al 1980;Baverel et al 1984). The net provision of energy during glutamine metabolism results from both complete oxidation of its carbon skeleton and, to a lesser extent, gluconeogenesis (Halperin et al 1982). Therefore, irrespective of the relative importance of complete oxidation and glucose synthesis from glutamine, this amino acid appears to be an energy supplier to the proximal tubule of fed rats.…”
Section: Adaptative Changes In Fuel Selection By the Rat Kidney Durinmentioning
confidence: 99%